THE LEARNING AND TEACHING OBJECTIVES IN ISLAMIC EDUCATION ACCORDING TO K.H. HASYIM ASH'ARI: Analysis Study of Âdâb al-‘Âlim wa al-Muta’allim Book - Syahrizal, Syahrizal (UIN Sumatera Utara, 2022)
Abstract: This study describes learning and teaching objectives according to K.H. Hasyim Asy'ari in the Âdâb al-'Âlim wa al-Muta'allim book. It was observed from the literature review, the descriptive method, content analysis, and reflective analysis employed that the learning and teaching objectives of K.H. Hasyim Asy'ari are theo-and humanistic-centric oriented. The learning objectives of K.H. Hasyim Asy'ari from one side need to be maintained, recommended, and adopted in Islamic education development because it is still very relevant to the context of contemporary Islamic education. But from the other side, the learning objectives of the ulama (scholar) need to be improved so that it does not ignore happiness in this world and the afterlife (ukhrawi). In addition to learning objectives, teaching objectives of K.H. Hasyim Asy'ari from one side need to be maintained, recommended, and adopted in the context of formulating and making policies on education and teaching objectives in Islamic education institutions because it is still very relevant to the context of contemporary in Indonesia. On the other hand, it also need to be improved so that the teaching objectives can be directed towards the interests of happiness in this world and the afterlife (ukhrawi).Keywords: Teaching and Learning Objectives, K.H. Hasyim Asy'ari, Âdâb al-'Âlim wa al-Muta'allim Book, Islamic education.